Mapping two decades of performance management and balanced scorecard research (2004–2024): trends, gaps, and emerging directions - Blahová, Michaela; Pálka, Přemysl; Anh Dao, Kim; Kwarteng, Michael Adu; Ntsiful, Alex (Transformations In Business & Economics, 2026)
This study conducts a comprehensive bibliometric analysis of 100 relevant research publications on performance management systems (PMS) and Balanced Scorecard (BSC) adoption from 2004 to 2024. While conducting the analysis, publication trends, influential authors, citations, and keywords are all taken into consideration in order to uncover the intellectual structure and development of the field. It is clear from the findings that the BSC continues to be an essential instrument for coordinating strategic goals with operational procedures. This is demonstrated by the fact that it is frequently mentioned and holds a central position in the research literature. Emerging topics such as sustainability, business intelligence, and technological integration are examples of how the focus on contemporary challenges is shifting along with the times. On the other hand, the study identifies research gaps, particularly in the areas of applications for the public sector and the incorporation of advanced digital tools.
Keywords: bibliometric analysis; performance management system; balance scorecard; adoption; systematic review